Diversidade fitoplanctônica: o papel de mudanças na dinâmica de uso em veredas e riachos - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Understanding how communities are distributed across space and time is one of the most studied subjects in ecology. Due to the intense anthropogenic actions on nature, it is crucial to understand how the different species respond to those anthropogenic doing. Land use is one of the main anthropogenic impact that is changing nature, which effects on both terrestrial and aquatic ecosystems. Our main goal was to test whether and how the land use, and physical and chemical conditions of the water respond to the spatial variables and verify how those acts upon phytoplankton taxonomic and functional diversity in headwater streams and palm swamps habitats. We hypothesize that (i) land use would have a direct and significant effect on the limnological features; (ii) that both land use and limnological variables would be spatially structured and also (iii) that only environmental variables (land use and limnological) would act upon the biodiversity indexes and that space would not demonstrate such effect. To test our hypothesis we sampled 41 habitats (headwater streams and palm swamps) from the Cerrado biome during the dry season in 2016 and 2017. To estimate the taxonomic diversity we used species richness, density, Shannon-Wiener index and biovolume. Functional richness (FRic), functional dispersion (FDis), functional evenness (FEve) and the community-weighted mean trait (CWM) were the components used to measure the functional diversity. We constructed a structural equation model (SEM) to evaluate the direct and indirect effects within abiotic variables (limnological, land use, and spatial) and the effect of them on the biotic variables (taxonomic and functional indexes). Among the land use variables, only land use change, through a timespan of one year, was selected in the model while conductivity was the only one selected among the limnological variables. In general, the land use was spatially structured while neither the limnological nor the biologic were affected directly by space, even though the biodiversity was indirectly affected by space through use change. Similarly, the land use also had no impact detected on the limnological variables. The structure model explained most of the taxonomic (r2adj= 0.8) and functional diversity (r2adj= 0.78). However, land use change accounted for most of that variation leaving aside the spatial and limnological variables. Our results highlight the importance that land use variables, especially the shifts in use from one year to another, have on the stream biota, affecting both taxonomic and functional diversity of phytoplankton.
Keywords: Conservação; Diversidade; Veredas; Riachos; Traços; SEM; Conservation; Diversity; Palm swamps; Headwaters; Traits; SEM; CONSERVACAO DA NATUREZA::CONSERVACAO DE BACIAS HIDROGRAFICAS